Isolation and identification of dye degrading bacteria from textile sludge to eradicate environmental hazards and maintain a sustainable environment - Kamal, Afia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.